2019
DOI: 10.24869/psyd.2019.69
|View full text |Cite
|
Sign up to set email alerts
|

Double Blind Controlled Study of Adding Folic Acid to Fluoxetine in the Treatment of Ocd

Abstract: Background: Folate is important for the synthesis of serotonin the neurotransmitter which plays a main role in OCD. We, therefore, explored the efficacy of folic acid as add on treatment to fluoxetine in a double blind study among patients with OCD. Subjects and methods: A double blind, 12-week study comparing the efficacy of folic acid as add on treatment and placebo in patients with OCD was conducted on thirty six (36) patients. Patients were randomly assigned to folic acid (5 mg/day) or placebo group in add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Table 1 lists the characteristics of each study and the characteristics of patients included in each study. Eicosapentaenoic acid (1 study) [ 41 ], folic acid (1 study) [ 43 ], lithium (1 study) [ 55 ], N -acetylcysteine (10 studies) [ 44 – 47 , 49 54 ], inositol (3 studies) [ 39 , 40 , 48 ], and silymarin (1 study) [ 42 ] were the mitochondrial modulators studied. Twelve studies included individuals with OCD [ 39 41 , 43 47 , 50 , 51 , 53 , 55 ], four others included individuals with trichotillomania [ 42 , 48 , 52 , 54 ], and the remaining study included individuals with excoriation disorder [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 lists the characteristics of each study and the characteristics of patients included in each study. Eicosapentaenoic acid (1 study) [ 41 ], folic acid (1 study) [ 43 ], lithium (1 study) [ 55 ], N -acetylcysteine (10 studies) [ 44 – 47 , 49 54 ], inositol (3 studies) [ 39 , 40 , 48 ], and silymarin (1 study) [ 42 ] were the mitochondrial modulators studied. Twelve studies included individuals with OCD [ 39 41 , 43 47 , 50 , 51 , 53 , 55 ], four others included individuals with trichotillomania [ 42 , 48 , 52 , 54 ], and the remaining study included individuals with excoriation disorder [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eicosapentaenoic acid (1 study) [ 41 ], folic acid (1 study) [ 43 ], lithium (1 study) [ 55 ], N -acetylcysteine (10 studies) [ 44 – 47 , 49 54 ], inositol (3 studies) [ 39 , 40 , 48 ], and silymarin (1 study) [ 42 ] were the mitochondrial modulators studied. Twelve studies included individuals with OCD [ 39 41 , 43 47 , 50 , 51 , 53 , 55 ], four others included individuals with trichotillomania [ 42 , 48 , 52 , 54 ], and the remaining study included individuals with excoriation disorder [ 49 ]. Thirteen studies included adults [ 39 41 , 43 , 44 , 47 51 , 53 55 ], three others included children [ 45 , 46 , 52 ], and one included both adults and children [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adding folic acid to fluoxetine did not significantly change the Y-BOCS total scores and response rate. The authors concluded that adding folic acid to fluoxetine had no benefits for OCD treatment [91]. In the end, five of 12 were assessed "much" or "very much improved" on the clinician-rated CGI, six were "minimally improved," and one showed "no change."…”
Section: Folic Acidmentioning
confidence: 99%